Mechanistic origin of grain size and oxygen interstitial effects on strain-induced α ” martensitic transformation in Ti-12Mo alloy - Yan Chong; Tomohito Tsuru; Masatoshi Mitsuhara; Baoqi Guo; Reza Gholizadeh; Koji Inoue; Andrew Godfrey; Nobuhiro Tsuji (Communications Materials)
Abstract Strain-induced α ” martensitic phase transformation (SIMT) critically affects the mechanical properties of metastable β titanium alloys. In this study, the effects of β grain size and oxygen content on SIMT in a Ti-12wt.%Mo alloy were systematically investigated. It is found that SIMT is promoted by a decrease in grain size and in oxygen content. The mechanistic origins of the anomalous grain size dependency and the acute oxygen content dependency of SIMT are discussed based on multi-scale microstructural characterization and state-of-the-art simulations. In the Ti-12wt.%Mo alloy, in-situ synchrotron X-ray diffraction analysis reveals that SIMT occurs before macroscopic yielding and only leads to elastic deformation of the surrounding β matrix due to the small transformation strain. Therefore, grain refinement does not raise the energy barrier for SIMT but rather provides more nucleation sites for strain-induced α ” martensite, thereby promoting SIMT in fine-grained Ti-12wt.%Mo alloy. In contrast, for the Ti-12wt.%Mo-0.3 wt.%O alloy, oxygen atoms substantially increase the energy barrier for SIMT, due to a change in the local configuration of oxygen atoms during the phase transformation. In addition, atom probe tomography reveals for the first time that oxygen atoms segregate at α ”/β phase boundaries, thereby further restricting the growth of α ” martensite.